ANALISIS PROFITABILITAS EKlJITAS KOPERASI DI KOTA SURABAYA - Ady Soejoto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2004)
The focus of this research was the change of profitability of co-operation equity in Suarabaya. The samples amount were 175 from 318 primary cooperative which were the annual meeting members. The data were collected from book years 1998 to 2002. That were the responsibility report of it’s official member about the cooperative movement. The result of this research indicated that the influence of change of principle deposit, obligatory deposit, debt and reserve to change of co-operation equity profitability were significant. The dominant contribution was the change of deposit obligatory, flollowed by the change of reserce. The prediction of net income toward the change of capital structure of equity especially change tha internal expenditure of  co-opertion. It’s dominant change toward the obligatory daposit sharpen the co-operation character, that member were the owner of client and capital.The .fhcus  '?f' this  research   was   the  change  <f rm?filahility   <?f' co-operation  equity  in Surabaya.  The samples  amount  were   175from   J /H  primary   cooperative  which  were  the annual  meeting  members.  The data  were  collected from   hook years   199H  to 2002,  Jhat were  the  responsibility   report  <?/'it's  <?f/icial  memher  ahout  the  cooperali\'e   movement. The  result  of  this  research  indicated  that  the  in.fluence  <?f' change  of principle   deposit, obligatory  deposit,  deht a11d  reseri·e  to change  < t' co-operation  equi y pr<?fitability   were significant.   The dominant   contribution  was  the change  <?(deposit  ohligatory, followed    by the  change  ,4·reseri·e.  The prediction   <?f' net  income  toward  the  change  of  capital structure   of  equi v  especially  chmwe  the  internal  expenditure   <?l co-operation.  lt 's dominant change tmrard the obligatory deposit sharpen the co-operation character, that member were the owner <f client and capital